Does experience rating reduce disability inflow? - Tomi Kyyrä; Juha Tuomala (Institute for the Study of Labor (IZA), 2013)
This study explores whether the experience rating of employers' disability insurance premiums affects the inflow of older employees to disability benefits in Finland. To identify the causal effect of experience rating, we exploit a pension reform that extended the coverage of the experience-rated premiums. The results show that a new disability benefit claim can cause substantial cost to the former employer through an increased premium. Nonetheless, we find no evidence of the significant effects of experience rating on the disability inflow. The lack of the behavioral effects may be due to the complexity of experience rating calculations and/or limited employer awareness.
Keywords: J14; J26; H32; 330; experience rating; disability insurance; early retirement